2016
DOI: 10.1016/j.labeco.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of workplace bullying on sickness absence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In particular, discrimination, stigma and bullying have been reported to be elevated among employed people with disabilities compared to those without disabilities (31). Previous research has shown a link between the experience of these types of adverse workplace experiences and greater likelihood of sickness absence (32,33,34). Hence, people with disabilities may be more exposed to stressors such as discrimination and bullying in workplace settings, and these may contribute to greater likelihood of taking sickness absence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, discrimination, stigma and bullying have been reported to be elevated among employed people with disabilities compared to those without disabilities (31). Previous research has shown a link between the experience of these types of adverse workplace experiences and greater likelihood of sickness absence (32,33,34). Hence, people with disabilities may be more exposed to stressors such as discrimination and bullying in workplace settings, and these may contribute to greater likelihood of taking sickness absence.…”
Section: Discussionmentioning
confidence: 99%
“…6 months) by peers or superiors, against which defence or retaliation is hindered by the recognition of a formal or informal power imbalance [43]). Research also suggests that greater exposure to workplace bullying is associated with higher sickness absence [44] and levels of job insecurity and intention to leave a job [45]. Hence, exposure to these negative experiences while in the workplace may contribute to exit from the labour market among workers with disability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the temporal and spatial analysis of workplace bullying has been facilitated through the collection of longitudinal data and the secondary analysis of large scale studies (Ariza-Montes, Muniz R, Leal-Rodríguez, & Leal-Millán, 2016;Askew et al, 2012;Attell, Kummerow Brown, & Treiber, 2016;Eriksen, Hogh, & Hansen, 2016;Finne, Knardahl, & Lau, 2011;Lallukka, Rahkonen, & Lahelma, 2011). Adopting a multi-method approach broadens the researcher's opportunities to engage with individuals who may be experiencing workplace bullying.…”
Section: Quantitative Approaches -The Devil Is In the Detailmentioning
confidence: 99%